Unraveling the Complex Interplay Between Transcription Factors and Signaling Molecules in Thyroid Differentiation and Function, From Embryos to Adults - López-Márquez, Arístides; Carrasco-López, Carlos; Fernández-Méndez, Celia; Santisteban, Pilar (Frontiers in Endocrinology, 2021)
Thyroid differentiation of progenitor cells occurs during embryonic development and in the adult thyroid gland, and the molecular bases of these complex and finely regulated processes are becoming ever more clear. In this Review, we describe the most recent advances in the study of transcription factors, signaling molecules and regulatory pathways controlling thyroid differentiation and development in the mammalian embryo. We also discuss the maintenance of the adult differentiated phenotype to ensure the biosynthesis of thyroid hormones. We will focus on endoderm-derived thyroid epithelial cells, which are responsible for the formation of the thyroid follicle, the functional unit of the thyroid gland. The use of animal models and pluripotent stem cells has greatly aided in providing clues to the complicated puzzle of thyroid development and function in adults. The so-called thyroid transcription factors – Nkx2-1, Foxe1, Pax8 and Hhex – were the first pieces of the puzzle identified in mice. Other transcription factors, either acting upstream of or directly with the thyroid transcription factors, were subsequently identified to, almost, complete the puzzle. Among them, the transcription factors Glis3, Sox9 and the cofactor of the Hippo pathway Taz, have emerged as important players in thyroid differentiation and development. The involvement of signaling molecules increases the complexity of the puzzle. I this context, the importantance of Bmps, Fgfs and Shh signaling at the onset of development, and of TSH, IGF1 and TGFβ both at the end of terminal differentiation in embryos and in the adult thyroid, are well recognized. All of these aspects are covered herein. Thus, readers will be able to visualize the puzzle of thyroid differentiation with most – if not all – of the pieces in place.